Tibial plateau fracture and RNA sequencing with osteogenesis imperfecta: a case report - Chen, Yixiao; Li, Guoqing; Wei, Liangchen; Weng, Jian; Liu, Su; Gu, Mingxi; Liu, Pei; Zhu, Yuanchao; Xiong, Ao; Zeng, Hui; Yu, Fei (Frontiers in Endocrinology, 2023)
Osteogenesis imperfecta (OI) is a hereditary skeletal dysplasia with an incidence of approximately 1:15,000 to 20,000. OI is usually caused by the mutation of COL1A1 and COL1A2, which would encode the α-chain of type I collagen. OI is clinically characterized by decreased bone mass, increased risk of bone fragility, blue sclerae, and dentinogenesis. Case presentation A 29-year-old male patient was diagnosed with right tibial plateau fracture caused by slight violence. Physical examination revealed the following: height, 140 cm; weight, 70 kg; body mass index (BMI), 35.71 kg/m2; blue sclera and barrel chest were observed. X-ray examination showed left convex deformity of the thoracic vertebrae with reduced thoracic volume. Laboratory examinations revealed a decrease in both vitamin D and blood calcium levels. Bone mineral density (BMD) was lower than the normal range. After the preoperative preparation was completed, the open reduction and internal fixation of the right tibial plateau fracture were performed. Meanwhile, whole blood samples of this OI patient and the normal control were collected for RNA transcriptome sequencing. The RNA sequence analysis revealed that there were 513 differentially expressed genes (DEGs) between this OI patient and the normal control. KEGG-enriched signaling pathways were significantly enriched in extracellular matrix (ECM)–receptor interactions. Conclusion In this case, DEGs between this OI patient and the normal control were identified by RNA transcriptome sequencing. Moreover, the possible pathogenesis of OI was also explored, which may provide new evidence for the treatment of OI.